2016
DOI: 10.24081/nijesr.2016.1.0017
|View full text |Cite
|
Sign up to set email alerts
|

Level of Work Readiness Skills, Career Self-Efficacy and Career Exploration of Engineering Students

Abstract: This paper determines the results of work readiness skills, career self-efficacy and career exploration of a final year engineering students of a private university of Malaysia. Data were collected from 62 final year engineering students. Reliability analysis was conducted to measure the internal consistency of scale. Results show highly reliable scale range for each variable. Furthermore, level of work readiness skills, career self-efficacy and career exploration was calculated on the basis of their mean scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It is the readiness of responding to a situation and the developmental level of maturity to practice something (Baharuddin et al, 2017;Cabrera, 2020;Sagita et al, 2020). Work readiness is indicated as people's ability to complete certain tasks (Makki et al, 2016). There are 4 (four) aspects that affect one's work readiness, including (1) aspects of mental, emotional, and physical development;…”
Section: Work Readinessmentioning
confidence: 99%
“…It is the readiness of responding to a situation and the developmental level of maturity to practice something (Baharuddin et al, 2017;Cabrera, 2020;Sagita et al, 2020). Work readiness is indicated as people's ability to complete certain tasks (Makki et al, 2016). There are 4 (four) aspects that affect one's work readiness, including (1) aspects of mental, emotional, and physical development;…”
Section: Work Readinessmentioning
confidence: 99%
“…Self-Efficacy. Makki et al [55] found that engineering graduates had higher skill levels, had high self-efficacy, and were more eager to explore their career plans. In addition, universities can develop relevant training for them, making them highly employable.…”
Section: Mediating Role Of Decisionmentioning
confidence: 99%
“…Graduates need to have practical and academic readiness in carrying out work duties and responsibilities, so that they can support work performance and the success of the profession being carried out (Sagita, Hami, & Hinduan, 2020). Makki, Javaid, & Bano (2016) describe readiness to work as skills, knowledge, and attitudes that enable new graduates to be able to make positive contribution in the workplace. Purnawan, Santosa, & Kurniawan (2020) explain that readiness to work is a person's ability to be able to complete a job in accordance with the provisions without experiencing obstacles with maximum results in accordance with predetermined targets.…”
Section: Readiness To Workmentioning
confidence: 99%